A collection of psalms and hymns in the language of the Cree Indians of north-west America [electronic resource] - Horden, John, 1828-1893. (London : Society for Promoting Christian Knowledge, 1920)
Text entirely in Cree, in syllabic characters. Original ed. 1874. Cf. Pilling (Algonquian), p. 235. Electronic reproduction. Mode of access: Internet. 44